Revealing heterogeneity and damage response in the adult human utricle. - Luca,E; Ibeh,N; Yamamoto,R; Liang,W; Bennett,D; Lin,V; Chen,J; Lovett,M; Dabdoub,A (Nat Commun, 2025)
The human utricle is a vestibular organ essential for balance, a function that declines with age. With the aging population projected to double to 2 billion by 2050 and no pharmaceutical or biological treatments available, balance disorders represent a significant unmet medical need. The utricle is composed of sensory and non-sensory cells, which are closely related. Non-sensory cells have limited capacity to regenerate sensory cells and, therefore, are a relevant therapeutic target. In this work, we profile the cellular and transcriptional landscape of the adult human utricle and its early response to ototoxic damage using bulk and single-cell RNA-sequencing of patient-derived samples. We identify six transcriptionally distinct non-sensory cell types, including a previously uncharacterized supporting cell-like population, demonstrating utricular heterogeneity. Following aminoglycoside-induced damage, we detect early transcriptional changes consistent with a capacity to respond to ototoxic damage within 24 hours and potentially initiate a regenerative response via an early-responding cell population, providing a foundation for regenerative strategies for balance recovery.